2009
DOI: 10.1371/journal.pone.0004583
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genomic Analysis Implicates Haploinsufficiency of Multiple Chromosome 5q31.2 Genes in De Novo Myelodysplastic Syndromes Pathogenesis

Abstract: Deletions spanning chromosome 5q31.2 are among the most common recurring cytogenetic abnormalities detectable in myelodysplastic syndromes (MDS). Prior genomic studies have suggested that haploinsufficiency of multiple 5q31.2 genes may contribute to MDS pathogenesis. However, this hypothesis has never been formally tested. Therefore, we designed this study to systematically and comprehensively evaluate all 28 chromosome 5q31.2 genes and directly test whether haploinsufficiency of a single 5q31.2 gene may resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 23 publications
(27 reference statements)
4
39
0
2
Order By: Relevance
“…25,26 In addition, other genes involved in cell cycle regulation, CDC25C and CDC23, and in chromatin modification, JMJD1B, a lysine-specific histone demethylase and previously described candidate ts gene from 5q 27 are localized in this segment. A recently described study of exon sequencing for all genes from this segment revealed no mutations in any of these genes, 28 further supporting the notion that the haploinsufficiency of one or more genes from this interval is the disease mechanism. It was described that the dual-specific phosphatase CDC25C is inhibited by lenalidomide and that expression of this gene was lower in AML and MDS with del(5q); 29 therefore, haplodeficiency of proteins might also have a role.…”
Section: Discussionsupporting
confidence: 70%
“…25,26 In addition, other genes involved in cell cycle regulation, CDC25C and CDC23, and in chromatin modification, JMJD1B, a lysine-specific histone demethylase and previously described candidate ts gene from 5q 27 are localized in this segment. A recently described study of exon sequencing for all genes from this segment revealed no mutations in any of these genes, 28 further supporting the notion that the haploinsufficiency of one or more genes from this interval is the disease mechanism. It was described that the dual-specific phosphatase CDC25C is inhibited by lenalidomide and that expression of this gene was lower in AML and MDS with del(5q); 29 therefore, haplodeficiency of proteins might also have a role.…”
Section: Discussionsupporting
confidence: 70%
“…Candidate generesequencing studies have not identified a biallelic gene mutation on either interval, suggesting that gene haploinsufficiency is the genetic mechanism contributing to MDS initiation and progression. 9 Using an shRNA screen in primary human CD34 ϩ cells, haploinsufficiency of RPS14 on the distal 5q33 region was found to contribute to the abnormal erythroid differentiation and apoptosis that is commonly observed in patients with the 5q Ϫ syndrome. 10 A mouse model that is haploinsufficient for Rps14 and 7 other genes is characterized by macrocytic anemia, further supporting the hypothesis that RPS14 haploinsufficiency is an important MDS-initiating event.…”
Section: Karyotype Abnormalities In Mds and Gene Haploinsufficiencymentioning
confidence: 99%
“…[1][2][3] The commonly deleted segment in 5q31.2 has been mapped, 4,5 and mutational analysis of the residual nondeleted allele has not identified a classic tumorsuppressor gene. [4][5][6] Therefore, we and others hypothesize that haploinsufficiency of a gene(s) in 5q31.2, not the loss of both alleles, may be a critical initiating event in MDS pathogenesis and may contribute to acute myeloid leukemia (AML) transformation when combined with additional cooperating mutations.The minimally deleted region on chromosome 5q31.2 is distinct from the minimally deleted region on 5q33.1, 7 which is associated with the 5q minus syndrome and carries a lower risk of progressing to AML compared with 5q31.2 deletions. Haploinsufficiency of the RPS14 gene, located in the 5q33.1 region, causes abnormal erythroid differentiation and accelerated apoptosis both in vitro and in a murine knockout model, supporting its role in the pathogenesis of the 5q minus syndrome.…”
mentioning
confidence: 99%
“…HSPA9 mRNA levels are reduced by 50% in CD34 ϩ -purified hematopoietic progenitors isolated from patients with del(5q) MDS compared with MDS patients without del(5q) and normal control CD34 ϩ cells, consistent with haploinsufficient expression levels in del(5q) patients. 6 An N-ethyl-N-nitrosourea mutagenesis screen in zebrafish identified that a bi-allelic mutation in Hspa9 resulted in anemia, dysplastic immature erythroblasts, accelerated apoptosis, and leukopenia. 15 Heterozygous Hspa9 mutant fish also displayed accelerated apoptosis in erythroid cells consistent with ineffective hematopoiesis.…”
mentioning
confidence: 99%